Pengaruh Strategi React dengan Media Pembelajaran Berbasis Prezi terhadap Kemampuan Komunikasi Matematis - Fany Aviola Vanka; Meyta Dwi Kurniasih (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to determine whether or not there is an effect of using the REACT strategy with Prezi-based learning media on mathematical communication skills. This type of research is quantitative using a quasi-experimental research method. The population in this study were all seventh grade students at SMP Negeri 194 Jakarta for the 2020/2021 academic year. The sample used was 66 students from class 2 class. Sampling using simple random sampling technique. The research instrument is in the form of a description question. The results of the normality test showed that the experimental class data were normally distributed and the control class data were not normally distributed. Hypothesis testing using a non-parametric test, namely the Mann Whitney test with a significant level of 5%, the value z_table=z_0.5(1-0.05) =z_0.475=1.96; because the value of z_count = 5.40. So that in determining the test criteria, the acceptance of Ha is: z_hitung>z_table. The results of this study can be concluded that there is an effect of REACT strategy with Prezi-based learning media on students' mathematical communication skills. Keywords: REACT Strategy, Prezi Learning Media, Students’ Mathematical Communication